Telomeres and stress in yeast cells: When genes and environment interact. Issue 5 (May 2020) - Harari, Yaniv; Gershon, Lihi; Alonso-Perez, Elisa; Klein, Shir; Berneman, Yael; Choudhari, Karan; Singh, Pragyan; Sau, Soumitra; Liefshitz, Batia; Kupiec, Martin
Abstract: Telomeres are structures composed of simple DNA repeats and specific proteins that protect the eukaryotic chromosomal ends from degradation, and facilitate the replication of the genome. They are central to the maintenance of the genome integrity, and play important roles in the development of cancer and in the process of aging in humans. The yeast Saccharomyces cerevisiae has greatly contributed to our understanding of basic telomere biology. Our laboratory has carried out systematic screen for mutants that affect telomere length, and identified ∼500 genes that, when mutated, affect telomere length. Remarkably, all ∼500 TLM (Telomere Length Maintenance) genes participate in a very tight homeostatic process, and it is enough to mutate one of them to change the steady-state telomere length. Despite this complex network of balances, it is also possible to change telomere length in yeast by applying several types of external stresses. We summarize our insights about the molecular mechanisms by which genes and environment interact to affect telomere length.